Reactive synthesis for porous TiVAlC ceramics by TiH2, V, Al and graphite powders. Issue 20 (15th October 2021) - Zou, Haoran; Li, Xide; Zhang, Chuo; Wen, Yi; Fan, Yiquan; Liu, Yuzuo; Xiong, Lieqiang; Zheng, Xiao; Yang, Junsheng
Abstract: Using the mixed powder of TiH2, graphite, aluminum and vanadium as starting materials, porous TiVAlC ceramics were fabricated by the reactive synthesis technology at 1300 °C. The chemical steadiness of porous TiVAlC along with the effects of sintering temperature on the viscous permeability coefficient, strength, porosity, pore size and volume expansion rate of the porous TiVAlC were explored, and the mechanism of pore formation was also revealed. The preparation process includes five steps as follows: (i) the complete decomposition of stearic acid at 500 °C; (ii) the pyrolysis of TiH2 at 700 °C, converting TiH2 into hydrogen and titanium (iii) The solid-liquid chemical reaction of solid vanadium, titanium and molten aluminum at 700 °C, converting the mixture into V–Al and Ti–Al compounds; (iv) At 900–1100 °C, Surplus V and Ti interact with graphite to synthesize carbides of TiVC2, VC, and TiC; (v) Reactive synthesized carbides (TiVC2, VC, and TiC), Ti2 AlC, V–Al and Ti–Al compounds that yield porous TiVAlC at 1300 °C.